A review of intrauterine device placement during caesarean section at level two facilities in the Metro West, Cape Town - Schutte, Marcelle (Department of Obstetrics and Gynaecology, 2021)
Study rationale In the Western Cape there are many intrauterine contraceptive devices (IUDs) inserted during caesarean section (C/S). Little is known about the long-term outcomes in the Metro West area. Objective To assess placement of IUDs at C/S and describe follow-up, with a view to compile best practice guidelines for insertion and follow-up in our clinic setting. Method A retrospective descriptive audit of clinical records was performed of all women who received an IUD at C/S between January and June 2018 at Mowbray Maternity Hospital (MMH) and New Somerset Hospital (NSH) in Cape Town. Results There were 2310 and 1376 C/S performed at MMH and NSH respectively. The IUD insertion rate was 17.4% (n=402) at MMH and 14.3% (n=197) at NSH. Almost two third of insertions were performed at the time of emergency caesarean section (59.1%; n=276). The majority of women experienced no immediate complications (84.4%). Only 77 women attended follow-up. The continuation rate at follow-up was 71.6%. The overall expulsion rate in hospital and at follow-up was 3%. Strings were visible in 53.2% of patients. An ultrasound was performed in 67.5 % (52/77) of patients. The IUD removal rate at follow-up was 24.7% (19/77). Discussion The poor follow-up rate is concerning, and measures must be taken to address this. The continuation rate of 71.6% is lower than expected but may have been biased by the low follow-up rate. Continuation rates improved with the experience of inserters which highlights the importance of training and supervision. Conclusion The immediate postpartum period may be the only opportunity to provide long acting reversable contraception to some women. In our study population follow-up rates are poor and therefore conclusions are difficult to accurately gauge. Measures must be taken to improve follow-up.